1945
DOI: 10.1084/jem.81.2.193
|View full text |Cite
|
Sign up to set email alerts
|

The Preparation and Properties of Influenza Virus Vaccines Concentrated and Purified by Differential Centrifugation

Abstract: Influenza virus vaccines containing from 1 to 10 mg. of virus materials per cc. concentrated and purified from infectious allantoic fluids by means of one or two cycles of differential centrifugation and inactivated by different treatments have been prepared and subjected to laboratory tests. Suitable inactivation of the virus preparations with retention of full red cell agglutinating activity and immunizing potency in mice was achieved by treatment with minimal amounts of formaldehyde or ultraviolet light. Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1945
1945
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…Friedenreich [10] carried out extensive studies of the phenomenon and demonstrated the enzymatic nature of the agent. In the ensuing years twenty-one cases have been reported which are believed by some to be the examples of the occurrence of this phe nomenon in vivo [18,11,1,2,9,14,19,15,12,25,22,27,20,13]. The validity of the relationship of these cases to the Thomsen-Friedenreich phenomenon will be discussed later.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Friedenreich [10] carried out extensive studies of the phenomenon and demonstrated the enzymatic nature of the agent. In the ensuing years twenty-one cases have been reported which are believed by some to be the examples of the occurrence of this phe nomenon in vivo [18,11,1,2,9,14,19,15,12,25,22,27,20,13]. The validity of the relationship of these cases to the Thomsen-Friedenreich phenomenon will be discussed later.…”
Section: Discussionmentioning
confidence: 98%
“…PR8-infected chicken allantoic fluid was purified by differential ultracentri fugation [25] followed by dialysis of the pellets against 0.15 M sodium chloride (referred to as saline). The extinction coefficient E using an extinction coefficient E (280 mp) of 15 [7].…”
Section: Isliker Straussmentioning
confidence: 99%
See 1 more Smart Citation
“…Friedenreieh [lo] carried out extensive studies of the phenomenon and demonstrated the enzymatic nature of the agent. In the ensuing years twenty-one cases have been reported which are believed by some t o be the examples of the occurrence of this phenomenon in vivo [18,11,1,2,9,14,19,15,12,25,22,27,20,131. The validity of the relationship of these cases t o the Thomsen-Friedenreich phenomenon will be discussed later.…”
Section: Discussionmentioning
confidence: 99%
“…46: 2156-2159(Oct. 1, 1946 The widespread use of the chick embryo for the cultivation of viruses and the markedly increased use of antigenic materials from this source for human vaccination make it desirable that influeniza virus obtained from chick embryos be highly refined in order to eliminate or reduce the possibilities of sensitizing human beings to chickembryo proteins. Of the various methods that have been devised to concentrate influenza virus so as to secure a more potent preparation for use as an immunizing vaccine, the one developed by Stanlev (1,2) and by Taylor et al (3), in which the Sharples Laboratory's SuperCentrifuge is used, appears to be the method of choice for obtaining concentrated and purified preparations relatively free from large amounts of inactive nonviral protein.…”
mentioning
confidence: 99%